Development of a liquid inerted microwave pyrolysis process - Shepherd, Benjamin John (2020)
The research presented in this thesis evaluates the potential of a new approach to carrying out pyrolysis. A pyrolysis process was demonstrated that combined microwave heating with an external liquid medium at atmospheric pressure. Generally, gases such as nitrogen are used to inert pyrolysis, however in this research liquids were used which had the benefit of acting as a heat-sink to maintain the external temperature at the atmospheric boiling point of the liquid.